Study of The Ecosysytem-friendly Fishing Port and Village Construction and Improvement Method - Koyama, Koukiti; Kodama, Izumi; Kida, Sanji (PROCEEDINGS OF CIVIL ENGINEERING IN THE OCEAN, 1996)
When constructing and improving fishing ports and villages, fundamental concepts bases on ecological aspects are required to recognize the value of the ecosysytem and to coexist with nature. As a first step to assess the construction and improvement of fishing ports and villages from ecological viewpoints, we conducted the following surveys and studies. We conducted a questionnaire survey on the natural environments and the living conditions of wildlife in fishing ports, as well as on the habitat conditions of the wildlife listed in the category subject to assessments, in our country. Furthermore, the ecosystem-friendly fishing port construction and improvement method was examined to conserve and restore the ecosystem around fishing ports.